QUALITY ANALYSIS AND RESTRAINT OF PROCESS PNPM-MPd INFRASTRUCTURE AREA OF JALAN RABAT BETON CASE STUDY: IN THE VILLAGE KEBALANPELANG SUB DISTRIK BABAT REGENCY LAMONGAN ESTI - Abidin, Zainul (EXTRAPOLASI: Jurnal Teknik Sipil, 2013)
Poor is one of social problems that canât be resolved fill reght now. The care accures through allcountries in the world and has difficull resolving, till this case still accure in many country. The dividing ofthis case is not only the responsibility of each goverment, but also the responsibility of itâs own society. Howover theer effort is in order to be able to fill the wellfere. One of the efforts is to develope the activiteis ofcountermeasuves of poor cases and opening the work field which is in PNPM lounched by goverment in2007 held in every fields specially in infrastructure basic praperation need by village sociaty. The step ofprocess of developing of facilities and infrastructures, basickly includes submiting activities planing,praperation and doing it the control of PNPM Mandiri Perdesaan held through monitoring, supervition,evaluation and reporting toword activities and the follow-up. The control toword the proces and activities ofPNPM Mandiri Perdesaan held be society propoused to empower all of inplementation. Based on the resultof analyzing of implementation process of monitoring helld be monitoring team a the activities andmeasuring the result of test helld in the field reach 225 kg/cm2 minimally and 306 kg/cm2 maximally morethan what lecanced by goverment 175 kg/cm2 ( PBIâ71) in implementations fo PNPM-MPd program showfilling the program technic based on anlizing and measuring of test result which held in the field with PTO.Keywords : Restraint, Efektif, PNPM-MPd